2012
DOI: 10.7439/ijbar.v3i6.335
|View full text |Cite
|
Sign up to set email alerts
|

Herbosomes - Herbal Drug in Novel Drug Delivery System for the Management of Periodontal Disease

Abstract: The effectiveness of any herbal medication is dependent on the delivery of effective level of the therapeutically active compounds. Herbosomes are recently introduced herbal formulations that are better absorbed and as a result produce better bioavailability and actions than the conventional botanical extracts. Herbal excipients are non-toxic and compatible they have a major role to play in pharmaceutical formulation. Herbal medicines have been widely used all over the world since ancient times and have been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…[1] Herbosomes are recently introduced herbal formulations that have better bioavailability, low toxicity and better theurapetic actions than the conventional botanical extracts. [7] Aloin, (10-glucopyranosyl-1,8-dihydroxy-3hydroxymethyl-9(10H)-anthracenone), an active compound obtained from Aloevera, which is known as miracle herb. Aloin when undergoes semi-synthetic modifications shows better antimicrobial activity than the unmodified one.…”
Section: Discussion:-mentioning
confidence: 99%
“…[1] Herbosomes are recently introduced herbal formulations that have better bioavailability, low toxicity and better theurapetic actions than the conventional botanical extracts. [7] Aloin, (10-glucopyranosyl-1,8-dihydroxy-3hydroxymethyl-9(10H)-anthracenone), an active compound obtained from Aloevera, which is known as miracle herb. Aloin when undergoes semi-synthetic modifications shows better antimicrobial activity than the unmodified one.…”
Section: Discussion:-mentioning
confidence: 99%
“…The herbosome technique is noninvasive and passive. Herbosome components can be used in cosmetic and medicinal products and are nontoxic and nonmutagenic [20,21]. Hydrophilic solvent ethanol has now primarily replaced hazardous organic solvents such as tetrahydrofuran and dichloromethane, which are used in conventional procedures to generate herbosome complexes, enhancing their safety and potential for clinical applications.…”
Section: Safetymentioning
confidence: 99%
“…Research has demonstrated the hepatoprotective properties of soy phospholipids, which work in concert to protect the liver from toxins, alcohol, and other medications. Additionally, they have been shown to raise plasma levels of circulating HDL and help with blood cholesterol clearance [20]. Phospholipids with a particular affinity for biological membranes include phosphatidylcholine.…”
Section: Additional Advantagesmentioning
confidence: 99%
“…[3] There are several traditional herbal remedies used to treat and treat dental related conditions such as periodontitis as well as gingivitis. [4] This article attempts to use the best available evidence to demonstrate the scientific status of the subject and the need for further research to expand the current knowledge. [5] This overview presents various natural remedies that can help with periodontitis.…”
Section: Introductionmentioning
confidence: 99%